Front-line liquid biopsy for early molecular assessment and treatment of hospitalized lung cancer patients - Francesca Parisi; Giuseppa De Luca; Manuela Mosconi; Sonia Lastraioli; Chiara Dellepiane; Giovanni Rossi; Silvia Puglisi; Elisa Bennicelli; Giulia Barletta; Lodovica Zullo; Sara Santamaria; Marco Mora; et al. (Cancer Treatment and Research Communications)
Background: Molecular characterization is pivotal for managing non-small cell lung cancer (NSCLC), although this process is often time-consuming and patients’ conditions might worsen while molecular analyses are processed.Our primary aim was to evaluate the performance of “up-front” next-generation sequencing (NGS) through liquid biopsy (LB) of hospitalized patients with newly detected lung neoplasm in parallel with conventional diagnosis. The secondary aim included longitudinal monitoring through LB of patients with oncogenic alterations at baseline. Methods: We enrolled 47 consecutive patients immediately after hospitalization and radiological detection of symptomatic lung neoplasm. LB from peripheral blood was performed at baseline, in parallel with conventional biopsy (CB), when feasible. Additionally, LBs were repeated during treatment in patients with actionable gene alterations at baseline. Oncomine™ Lung cfTNA Research Assay panel was employed for processing plasma samples in NGS. Results: 47 hospitalized patients were enrolled. LB identified 28 patients with gene alterations, including mutations of EGFR (n = 7), KRAS (n = 12), ERBB2 (n = 1), TP53 (n = 2), BRAF (n = 1), one ALK rearrangement, and 4 patients with combined mutations involving EGFR, KRAS and PIK3CA.LB and CB were consistent, except for two patients. Three patients with positive LB for oncogenic drivers did not undergo CB due to contraindications.Median time to molecular results after LB was significantly lower compared to time to molecular report after CB (11 versus 22 days, p < 0.001). Conclusions: Despite limited numbers, our study supports the role of front-line LB for improving management of symptomatic patients with lung cancer, potentially leading to early targeted therapy initiation.